Unusual activity pattern of leucine aminopeptidase inhibitors based on phosphorus containing derivatives of methionine and norleucine - Pícha, Jan; Liboska, Radek; Buděšínský, Miloš; Jiráček, Jiři; Pawełczak, Małgorzata; Mucha, Artur (Journal of enzyme inhibition and medicinal chemistry, 2011)
Ligands containing bulky aliphatic P1 residues exhibit a high affinity towards cytosolic leucine aminopeptidase, a bizinc protease of biomedical significance. According to this specificity, a series of phosphonic and phosphinic compounds have been put forward as novel putative inhibitors of the enzyme. These phosphonic and phosphinic compounds were derivatives of methionine and norleucine as both single amino acids and dipeptides. The designed inhibitors were synthesised and tested towards the peptidase isolated from porcine kidneys using an improved separation procedure affording superior homogeneity. Unexpectedly, organophosphorus derivatives of methionine and norleucine exhibited moderate activity with K(i) values in the micromolar range.
Keywords: aktivace enzymů; Animals; Kidney; Enzyme Activation; fosfor; Molecular Structure; Enzyme Inhibitors; Methionine; leucylaminopeptidasa; prasata; Leucyl Aminopeptidase; norleucin; molekulární struktura; Norleucine; Phosphorus; Swine; inhibitory enzymů; methionin; zvířata; ledviny